Feminist Afterlives of the Witch - Kosmina, Brydie. author. aut Link
XV, 262 p. 1 illus.
Keywords: "Brydie Kosmina’s book is a smart, topical study of the figure of the witch in contemporary culture, sensitive and thought-provoking in its approach and written with flair and passion." --Professor Marion Gibson, University of Exeter, Devon UK. The book investigates the witch as a key rhetorical symbol in twentieth- and twenty-first century feminist memory, politics, activism, and popular culture. The witch demonstrates the inheritance of paradoxical pasts, traversing numerous ideological memoryscapes. This book is an examination of the ways that the witch has been deployed by feminist activists and writers in their political efforts in the twentieth century, and how this has indelibly affected cultural memories of the witch and the witch trials, and how this plays out in popular culture representations of the symbol through the twentieth and twenty-first centuries. Consequently, this book considers the relationship between popular culture and media,activist politics, and cultural memory. Using hauntological theories of memory and temporality, and literary, screen, and cultural studies methodologies, this book considers how popular culture remembers, misremembers, and forgets usable pasts, and the uses (and misuses) of these memories for feminist politics. Given the ubiquity of the witch in popular culture, politics and activism since 2016, this book is a timely examination of the range of meanings inherent to the figure, and is an important study of how cultural symbols like the witch inherit paradoxical memories, histories, and politics. The book will be valuable for scholars across disciplines, including witchcraft studies, feminist philosophy and history, memory studies, and popular culture studies. Brydie Kosmina is a Visiting Research Fellow at the University of Adelaide, Australia, in Tarndanya/Adelaide. Her research covers feminist memory, politics and popular culture, and the environmental humanities, particularly nuclear studies. She teaches and lectures in literary, screen and cultural studies. Brydie is a Postgraduate and Early Career Researcher Representative to the Cultural Studies Association of Australasia, and works as an editor, writer and reviewer for indie arts and culture website Collage Adelaide.